A novel approach to chronic wound management using a patented cream of silicon dioxide, silver ions, chlorhexidine and hyaluronic acid. Issue 3 (2021) - Nair, Harikrishna KR; Ilwani, Nur Zati; Ng, Ling Li
No abstract available